2019
DOI: 10.1080/15384101.2019.1629792
|View full text |Cite
|
Sign up to set email alerts
|

De novo lipogenesis at the mitotic exit is used for nuclear envelope reassembly/expansion. Implications for combined chemotherapy

Abstract: Mitosis has been traditionally considered a metabolically inactive phase. We have previously shown, however, that extensive alterations in lipids occur as the cells traverse mitosis, including increased de novo fatty acid (FA) and phosphatidylcholine (PtdCho) synthesis and decreased lysophospholipid content. Given the diverse structural and functional properties of these lipids, we sought to study their metabolic fate and their importance for cell cycle completion. Here we show that FA and PtdCho synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Furthermore, exogenous palmitate fails to reverse the inhibitory effect, suggesting that endogenously synthesized FAs are critical for completion of the cell cycle [ 104 ]. In a follow-up study, upregulation of endogenous FA synthesis is shown to be directed towards the nuclear envelope at the mitotic exit [ 105 ]. Nuclear localization of FASN was first reported in 2014 where it was shown to correlate with disease aggressiveness in prostate cancer [ 67 ].…”
Section: Fasn Influences Organelle Activity In Tumor Cellsmentioning
confidence: 99%
“…Furthermore, exogenous palmitate fails to reverse the inhibitory effect, suggesting that endogenously synthesized FAs are critical for completion of the cell cycle [ 104 ]. In a follow-up study, upregulation of endogenous FA synthesis is shown to be directed towards the nuclear envelope at the mitotic exit [ 105 ]. Nuclear localization of FASN was first reported in 2014 where it was shown to correlate with disease aggressiveness in prostate cancer [ 67 ].…”
Section: Fasn Influences Organelle Activity In Tumor Cellsmentioning
confidence: 99%
“…Indeed, live cell analysis confirms that reduced free fatty acid levels in G2 and mitosis can cause mitotic defects. Fatty acids that are synthesized late in the cell cycle are important for nuclear envelope formation 84 , possibly explaining why FASN inhibition in G2 can lead to mitotic defects. In this way, cells sense if there is insufficient lipid biosynthesis and halt the cell cycle by employing an anticipatory G1 lipid checkpoint that prevents the start of a typically over 12 hour-long process that would end in a defective mitosis when lipid composition is most critical.…”
Section: Discussionmentioning
confidence: 99%
“…Several agents that target specific metabolic pathways, including fatty acid synthesis, have been shown to have the therapeutic potential to improve cancer treatment efficacy. A reduction of key enzymes in the DNL pathway has been shown to cause a reduction in fatty acid products [27] and fatty acid oxidation (FAO) [12], resulting in a decrease in the proliferative, metastatic and invasive ability of cancer cells [67–76]. The mechanism of the anticancer effect of EGCG has been demonstrated to be mediated via inhibiting the fatty acid biosynthesis pathway [50,77–80].…”
Section: Discussionmentioning
confidence: 99%